2015
DOI: 10.1007/s10895-015-1672-4
|View full text |Cite
|
Sign up to set email alerts
|

Novel Coumarin Substituted Water Soluble Cyclophosphazenes as “Turn-Off” Type Fluorescence Chemosensors for Detection of Fe3+ ions in Aqueous Media

Abstract: In the present work, 3-[2-(diethylamino)ethyl]-7-oxy-4-methylcoumarin substituted cyclotriphosphazene (4) and cyclotetraphosphazene (5) derivatives were synthesized by the reactions of hexachlorocyclotriphosphazene (1) or octachlorocyclotetraphosphazene (2) with 3-[2-(diethylamino)ethyl]-7-hydroxy-4-methylcoumarin (3) for the first time. The quaternized cationic (6 and 7) and zwitterionic (8 and 9) derivatives of these compounds (4 and 5) were obtained by the reactions of dimethyl sulfate and 1,3-propanesulton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…The PzILs with different anions (chloride, Cl − , bis-trifluoromethane sulfonimide, NTf 2 − and tetrafluoroborate, BF 4 − ) were obtained by simple anion exchange reactions 17 , 20 25 . On the other hand, PzILs with various molecular weights or different average chain lengths have been used as antibacterial, antifungal and anticancer agents 5 , 6 , 13 – 15 , lubricants 17 , 25 , adsorbents and surface modifiers 18 , a gate dielectric layer for OFETs 20 , 21 , electrolyte solutions 19 , 23 , 24 and chemosensors for metal ions 26 .…”
Section: Introductionmentioning
confidence: 99%
“…The PzILs with different anions (chloride, Cl − , bis-trifluoromethane sulfonimide, NTf 2 − and tetrafluoroborate, BF 4 − ) were obtained by simple anion exchange reactions 17 , 20 25 . On the other hand, PzILs with various molecular weights or different average chain lengths have been used as antibacterial, antifungal and anticancer agents 5 , 6 , 13 – 15 , lubricants 17 , 25 , adsorbents and surface modifiers 18 , a gate dielectric layer for OFETs 20 , 21 , electrolyte solutions 19 , 23 , 24 and chemosensors for metal ions 26 .…”
Section: Introductionmentioning
confidence: 99%
“…Quaternized ionic and zwitterionic compounds display excellent solubility in water and the effects of metal ions on the fluorescent behavior of the cytophosphazene salts were investigated using these compounds as chemosensors for metal ions. The results showed that cyclophosphazenium salts exhibit highly selective fluorescence chemosensor behavior for Fe 3+ ions in aqueous solution [38].…”
Section: Chemosensors For Metal Ionsmentioning
confidence: 97%
“…PzILs are prepared by quaternization of a wide variety of phosphazenes either at the sidegroup or at the skeletal nitrogen atoms. These ILs have been used as anticancer, antibacterial reagents [31][32][33][34], adsorbents and surface modifiers of fluorescent nanoparticles [35], lubricants [36,37], chemosensors for metal ions [38], electrolyte solutions for energy storage devices [39][40][41], as gate dielectric layer for OFETs [42], or as polyelectrolytes [26,43,44].…”
Section: Applications Of Phosphazene-based Ionic Liquidsmentioning
confidence: 99%
“…In order to make these compounds water-soluble, hydrophilic groups should be present in the molecular structure. There are several examples of water-soluble phosphazenes in the literature, but to the best of our knowledge, most of them are focused on polyphosphazenes [23][24][25][26][27][28]. Thus, the design and synthesis of water-soluble cyclotriphosphazene compounds is particularly important for studies in aqueous media.…”
Section: Introductionmentioning
confidence: 99%